(untitled) (Proceedings of International Conference on Special Education, 2023)
The present study aimed to find out the quality of life of adolescents with intellectual disability. The study widely investigates the vital aspects related to the life of adolescents like basic living skills, social skills, domestic activities, community orientation, personal care, and emotional wellbeing. This study aims to find out the quality of life mainly through direct assessment and observation of adolescents.Descriptive method of research was employed for the study. The study sample consisted of 204 adolescents with intellectual disability, randomly selected from various special schools in Kottayam and Ernakulam district of Kerala state, in South India. Data on quality of life of these individuals were collected through a standardised Quality of life Scale of Adolescents with Intellectual Disability developed by the authors. The data were analysed through arithmetic mean and standard deviation. The result indicated that quality of life of adolescents with intellectual disability is of an average level. About 37% have a high or very high quality of life. Whereas the remaining 63% belong to average, low or very low quality of life.